Pengaruh Kualitas Pelayanan Klaim terhadap Keputusan Pembelian Polis Assuransi Kerugian pada PT Sompo Insurance Indonesia - Nahason Sitohang; Jon Fiter Hutapea (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of the quality of claims services on the purchase of PT loss insurance policies. Sompo Insurance Indonesia. This research approach is quantitative research. The data collection technique uses a questionnaire method. This research uses the Slovin technique so that the sample required in this research is 78 respondents from the customer population of PT Sompo Insurance Indonesia which is 350 using, then analysis is carried out with the data using validity tests, reliability tests, classical assumption tests, normality tests, heteroscedasticity tests and simple linear regression analysis. The results of the coefficient of determination test show the value of R Square = 0.605, so it can be concluded that the Claim Service Quality variable (X) influences the Policy Purchase Decision variable (Y) by 60.5% while the remainder is (100 – 60.5%) = 39.5 % influenced by other factors not included in this study. The results of the t test obtained a t-count value > t-table or (10.796 > 1.99167) with a Sig value. < 0.05 or (0.000 < 0.05). Thus, H0 is rejected and Ha is accepted, this shows that the Claim Service Quality variable has a significant influence on the decision to purchase a loss insurance policy at PT Sompo Insurance Indonesia.